2001
DOI: 10.1093/hmg/10.16.1649
|View full text |Cite
|
Sign up to set email alerts
|

The importance of gene dosage studies: mutational analysis of the parkin gene in early-onset parkinsonism

Abstract: Early-onset parkinsonism (EOP) may be associated with different mutations in the parkin gene, including exon deletions and duplications. To test for gene dosage alterations, we developed a new method of quantitative duplex PCR using the fluorescence resonance energy transfer technique on the LightCycler (Roche Diagnostics). In 21 patients with EOP, three mutations (a single base pair substitution in exon 3 and small deletions in exon 9) were detected by conventional mutational screening (single-strand conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(161 citation statements)
references
References 22 publications
7
152
0
2
Order By: Relevance
“…This technique was previously demonstrated to detect accurately Parkin mutations in a large number of patients at much higher frequencies. 6,27,28 With regard to the DJ-1 gene, recent studies demonstrated a mutation frequency between 1 and 2% among EOP patients. 7,8,15,16 Only two of the published investigations included testing for gene dosage alterations and, as expected, revealed higher mutation rates (2 versus 1%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique was previously demonstrated to detect accurately Parkin mutations in a large number of patients at much higher frequencies. 6,27,28 With regard to the DJ-1 gene, recent studies demonstrated a mutation frequency between 1 and 2% among EOP patients. 7,8,15,16 Only two of the published investigations included testing for gene dosage alterations and, as expected, revealed higher mutation rates (2 versus 1%).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PD was based on the UK Brain Bank diagnostic criteria (with the exception that positive family history was not regarded an exclusion criterion). 20 6 In all, 100 chromosomes of Italian and 100 chromosomes of German control individuals were screened for the presence of the novel mutations and the novel polymorphism. The mean age of the controls at the time of the blood collection was 52.2714.3 years.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…This points to disease-causing DNA changes localized in untranslated regions. In addition, deletions or duplications of the complete gene or single exons are not seen by the SSCP procedure but may be important in mutational analyses (Hedrich et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence was measured during the 551C step. Product concentration was calculated as described 5 and…”
Section: Mutation Analysismentioning
confidence: 99%